2017
DOI: 10.1016/j.addr.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Progress and opportunities for enhancing the delivery and efficacy of checkpoint inhibitors for cancer immunotherapy

Abstract: Despite the advent of immune checkpoint blockade for effective treatment of advanced malignancies, only a minority of patients respond to therapy and significant immune-related adverse events remain to be minimized. Innovations in engineered drug delivery systems and controlled release strategies can improve drug accumulation at and retention within target cells and tissues in order to enhance therapeutic efficacy while simultaneously reducing drug exposure in off target tissues to minimize the potential for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 103 publications
0
79
0
Order By: Relevance
“…High expression of CD86 by DCs motivated the exploration of the potential therapeutic synergies of immune checkpoint blockade with aCTLA‐4 mAb with pPTX/pCD‐pSNO treatment, as an engagement of DC‐expressed CD80/86 with CTLA‐4 instead of CD28 on T cells is well‐known to inhibit the expansion of T cells. [ 67,68 ] Indeed, co‐administration of PTX and aCTLA‐4 has been reported to lead efficient regression of tumor growth, effects associated with expansion of both activated CD8 + and CD4 + T cells. [ 12 ] As such, the therapeutic potential of aCTLA‐4 in pPTX/pCD‐pSNO treatments was investigated in a dual tumor model ( Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…High expression of CD86 by DCs motivated the exploration of the potential therapeutic synergies of immune checkpoint blockade with aCTLA‐4 mAb with pPTX/pCD‐pSNO treatment, as an engagement of DC‐expressed CD80/86 with CTLA‐4 instead of CD28 on T cells is well‐known to inhibit the expansion of T cells. [ 67,68 ] Indeed, co‐administration of PTX and aCTLA‐4 has been reported to lead efficient regression of tumor growth, effects associated with expansion of both activated CD8 + and CD4 + T cells. [ 12 ] As such, the therapeutic potential of aCTLA‐4 in pPTX/pCD‐pSNO treatments was investigated in a dual tumor model ( Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…With the assistance of platelets to recognize and interact with circulating tumor cells (CTCs), anti‐PD‐L1 successfully targeted CTCs in the blood circulation and surgical sites. Interestingly, such platelet‐delivery approaches could be activated in situ and effectively release anti‐PD‐L1 . Besides, their study showed that activated platelets could release inflammatory cytokines to amplify the local immune response, potentially improving the objective response rate.…”
Section: Carriers For Delivery Of Icb Inhibitorsmentioning
confidence: 99%
“…Infrequent but serious visceral organ inflammatory, sometimes life‐threatening toxicities have also been reported . Moreover, a significantly higher rate of adverse side effects is observed when in the ICB combination therapy …”
Section: Introductionmentioning
confidence: 99%
“…2 Moreover, standard therapy for lymphedema, one of the morbidities associated with both lymphatic filariasis infections and sentinel lymph node (LN) removal following breast tumor resection, employs only a combination of compression and physical therapy. 13 For diseases where the lymphatics are not the primary target but are critically involved in the disease pathology or may be useful therapeutically, such as immunotherapy 5,[14][15][16] or LN-directed chemotherapy (e.g., for the treatment of sentinel LN metastases) 17 , there exist few approved treatments that are specifically formulated to enhance delivery to lymphatics, leaving open the possibility of a range of undesired consequences including reduced treatment efficacy and toxicities related to accumulation in off target tissues. 18 A therapeutic of particular interest for the treatment of lymphatic-related diseases is nitric oxide (NO), an extremely promiscuous signaling molecule that takes part in a variety of physiological processes ranging from vasodilation, [19][20][21][22][23] to neural signaling, 24 to immune cell cytotoxic defenses.…”
Section: Introductionmentioning
confidence: 99%